2019
DOI: 10.1016/j.redox.2019.101250
|View full text |Cite
|
Sign up to set email alerts
|

Acute bilirubin ditaurate exposure attenuates ex vivo platelet reactive oxygen species production, granule exocytosis and activation

Abstract: Background Bilirubin, a by-product of haem catabolism, possesses potent endogenous antioxidant and platelet inhibitory properties. These properties may be useful in inhibiting inappropriate platelet activation and ROS production; for example, during storage for transfusion. Given the hydrophobicity of unconjugated bilirubin (UCB), we investigated the acute platelet inhibitory and ROS scavenging ability of a water-soluble bilirubin analogue, bilirubin ditaurate (BRT) on ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Platelet viability was assessed using a full-spectrum detector based (filter-less) Cytek Aurora Flow Cytometer (Cytek Biosciences Inc., Fremont, CA, USA) adapted from protocols published elsewhere [ 62 , 63 ]. Immunolabeling of CD41/61, a platelet-specific antigen, was carried out with a primary (CD41/61, monoclonal antibody CO.35E4, #MA5-28370 Invitrogen, Life Technologies Corporation, Carlsbad, CA, USA) and a secondary antibody conjugated with a fluorochrome (goat polyclonal anti-mouse IgG conjugated with R-phycoerythrin; #P-852, Invitrogen, Life Technologies Corporation, OR, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Platelet viability was assessed using a full-spectrum detector based (filter-less) Cytek Aurora Flow Cytometer (Cytek Biosciences Inc., Fremont, CA, USA) adapted from protocols published elsewhere [ 62 , 63 ]. Immunolabeling of CD41/61, a platelet-specific antigen, was carried out with a primary (CD41/61, monoclonal antibody CO.35E4, #MA5-28370 Invitrogen, Life Technologies Corporation, Carlsbad, CA, USA) and a secondary antibody conjugated with a fluorochrome (goat polyclonal anti-mouse IgG conjugated with R-phycoerythrin; #P-852, Invitrogen, Life Technologies Corporation, OR, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, although the different cell types exhibit varying degrees of sensitivity toward bilirubin toxicity, they all benefit from bilirubin cytoprotection at low concentrations. This has clinical implications, since recent research has shown that BRT prevents ROS generation in ex vivo platelets, opening the possibility of screening the actions of acute BRT treatment to improve platelets storage and function (Pennell et al, 2019).…”
Section: Biosynthesis Metabolism Bioavailability and Activitymentioning
confidence: 99%
“…Platelet viability was assessed using a full-spectrum detector-based (filterless) Cytek Aurora Flow Cytometer (Cytek Biosciences Inc, Fremont, CA, USA) adapted from protocols published elsewhere [ 26 , 27 ]. Immunolabeling of CD41/61, a platelet-specific antigen, was carried out with a primary (#MA5-28,370 Invitrogen, Life Technologies Corporation, OR, USA) and a secondary antibody conjugated with a fluorochrome (#P-852, Invitrogen, Life Technologies Corporation, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%